The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/adma.202102844
|View full text |Cite
|
Sign up to set email alerts
|

Exceptionally High Blocking Temperature of 17 K in a Surface‐Supported Molecular Magnet

Abstract: liquid-nitrogen temperature [3] or single atoms exhibiting extremely long magnetic relaxation times. [4][5][6] In particular, systems based on late lanthanide family elements, like Dy and Tb, have been largely in focus, including single-molecule, [2,3] singleatom, [4,5] or single-chain magnets. [7,8] Adsorption of SMMs on surfaces allows to study individual molecular units, as well as to realize transport schemes essential for the implementation of SMMs in molecular-scale spintronics or quantum computing devic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 45 publications
1
37
0
Order By: Relevance
“…S16 in ESI†). This proves that the X-ray irradiation considerably accelerates magnetic relaxation in Tb 2 @C 79 N. Such X-ray induced demagnetization was reported earlier in monolayers of metallofullerenes 61,62,96 and TbPc 2 , 46 but the effect in Tb 2 @C 79 N is more pronounced. Further measurements of (sub)monolayer films demonstrate that not only the demagnetization rate but also the population of valence orbitals may be affected by X-ray irradiation through secondary processes.…”
Section: Computational Modelingsupporting
confidence: 85%
See 2 more Smart Citations
“…S16 in ESI†). This proves that the X-ray irradiation considerably accelerates magnetic relaxation in Tb 2 @C 79 N. Such X-ray induced demagnetization was reported earlier in monolayers of metallofullerenes 61,62,96 and TbPc 2 , 46 but the effect in Tb 2 @C 79 N is more pronounced. Further measurements of (sub)monolayer films demonstrate that not only the demagnetization rate but also the population of valence orbitals may be affected by X-ray irradiation through secondary processes.…”
Section: Computational Modelingsupporting
confidence: 85%
“…[56][57][58][59][60][61][62] The nitride clusterfullerenes Dy 2 ScN@C 80 and DySc 2 N@C 80 were shown to maintain their SMM properties in monolayers on metallic substrates. [56][57][58][59][60] _ENREF_71_ENREF_73 Even more promising are recent studies of Dy 2 @C 80 (CH 2 Ph) deposited onto graphene 61 and Tb 2 @C 80 (CH 2 Ph) on graphene and HOPG, 62 which demonstrated that dimetallofullerenes with single-electron lanthanidelanthanide bonds can also sustain their superb SMM performance in monolayers. Magnetic hysteresis in these monolayers was observed at considerably higher temperatures than in all other surface-supported SMMs, reaching 28 K for a self-assembled monolayer of Tb 2 @C 80 (CH 2 Ph) derivative.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Fonin and co-workers were able to preserve the reported magnetic remanence of Dy 2 @C 80 (CH 2 Ph) on the graphene/Ir(111) surface exhibiting T B of 17 K at the field sweep rate of 2 T min −1 . 53 The integrating of SMM with hybrid materials usually diminishes its magnetic performance due to the formation of buffer environment between the substrate and magnetic materials; however, in this report, they were able to preserve magnetic remanence comparable with the original bulk system. 103 In addition, the utilization of paramagnetic bridging radical ligands enabling the establishment of strong magnetic coupling between the lanthanide centers under constrained coordination environments is becoming another successful strategy.…”
Section: ■ Strategies For Designing Hp−dy−smmsmentioning
confidence: 54%
“…Even slight overheating changes its mechanism from nucleophilic substitution to radical polyaddition, which produces intractable mixtures of EMF­(CH 2 Ph) n multiadducts. As di-EMFs with single-electron lanthanide–lanthanide bond are very robust SMMs and qubit candidates, ,,, development of a streamlined approach to their synthesis and separation would be very beneficial.…”
Section: Introductionmentioning
confidence: 99%